Educati al “desiderio” partendo dalla Bibbia - Parisi, Nicola (Alpha Omega, 2020)
Summary: Unlike other religious confessions, desire occupies a fundamental place in biblical revelation to the point of constituting a specific element in the relationship with God. The desire that arises from the wish to live can end with death, if someone gives way to the temptation to put their own self in the place of God or if they fail to measure up to the right relationship with others, turning them into an object instead of meeting them as a subject. “Do not covet” or “do not desire” in the commandments does not mean to suppress or to demonise the desires, but rather to educate them and to direct them towards the good. Therefore, we analyze desire as it is found in the sapiential and in the Gospel traditions, in such a way as to focus upon the educational-pedagogical criteria necessary to transmit to the next generations the ability to desire, since in today’s society this capacity has been lost. Key words: desire, gift, need, biblical revelation, relationship, education, the pedagogy of desire, blessing, transmission, happiness. Parole chiave: desiderio, dono, bisogno, rivelazione biblica, relazione, educazione, pedagogia del desiderio, benedizione, trasmissione, felicità.